Hydrogel-Based Active Substance Release Systems for Cosmetology and Dermatology Application: A Review - Martyna Zagórska-Dziok; Marcin Sobczak (MDPI AG, 2020)
Hydrogels are playing an increasingly important role in medicine and pharmacy. Due to their favorable physicochemical properties, biocompatibility, and designed interaction with living surroundings, they seem to be one of the most promising groups of biomaterials. Hydrogel formulations from natural, semi, or synthetic polymeric materials have gained great attention in recent years for treating various dermatology maladies and for cosmetology procedures. The purpose of this review is to present a brief review on the basic concept of hydrogels, synthesis methods, relevant mechanisms, and applications in dermatology or cosmetology. This review discusses transdermal therapies and the recent advances that have occurred in the field.